Remake of Survival Horror Video Game and How It’s Implemented: Comparative Analysis on Original and Remake Version of Resident Evil 4 - Pratama, Galih Dea; Shiddiqi, Hafizh Ash; Hermawan, Eric Savero; Novika, Andien Dwi; Ardiyanto, Elshad Ryan (Bina Nusantara University, 2024)
Video game is particularly known as an interactive media designed to present entertainment among its targeted users. While being released from time to time, there comes the desire to provide the outdated games to the modern audiences, hence surfaces the trend of video game remakes, which recently presented through Resident Evil 4 that serves as the newer version to the original one released in 2005. To give better understanding on the games, there is Elemental Tetrad which emphasizes on four elements like Mechanics, Story, Aesthetics and Technology. In this research, Elemental Tetrad is utilized to analyze both versions of Resident Evil 4, diving deep into how the game elements are implemented by the games while also highlighting the advances presented in the remake version compared to the original one. There are various differences of both games, such as the existence of more new mechanics, the expanded story and characterizations, slight change in the aesthetics to accommodate the realism of the remake, with all are enabled through the usage of latest RE Engine.